IL-6 Promotes Hepatocellular Carcinoma Invasion by Releasing Exosomal miR-133a-3p - Xudong Ren; Yu Zhou; Yunling Luo; Chaoqun Wang; Anna Pan; Yanqin Ju; Haoting Sun; Zhifei Lin; Beiyuan Hu; Guangzheng Sun; Wenwei Zhu; Liang Hong (Gastroenterology Research and Practice)
Interleukin-6 (IL-6), an important inflammatory cytokine, is a key factor regulating cancer metastasis. Cancer cells can modulate their tumorigenic abilities by sorting specific microRNAs (miRNAs) as exosomes into the tumor microenvironment. The relationship between IL-6 and exosomal miRNAs related to hepatocellular carcinoma (HCC) metastasis remains to be elucidated. We examined the metastatic ability of HCC cells after IL-6 treatment and found that miR-133a-3p was sorted into exosomes after IL-6 stimulation and was subsequently released into the tumor microenvironment. In vitro analysis confirmed that exosomal miR-133a-3p acted as a tumor suppressor in HCC. Bioinformatic analysis revealed several signaling pathways and hub genes (CREB1, VCP, CALM1, and YES1) regulated by miR-133a-3p. Survival curves further verified the important roles of hub genes in the prognosis of patients with HCC. It is envisaged that the IL-6/miR-133a-3p axis may be related to the activation of CREB1, VCP, CALM1, and YES1. Our findings provide new insights into the role of exosomal miRNA-mediated tumor progression under inflammatory conditions.